Phytoplankton chlorophyll-breakdown pathway: Implication in ecosystem assessment. (15th March 2020) - Sathish, K.; Patil, J.S.; Anil, A.C.
Abstract: The chlorophyll-breakdown to pheophorbide is determined by biotic factors such as grazing (via chlorophyllide) or senescence (via pheophytin). So far, much of the information on chlorophyll-breakdown is available from sediments, but information from the water column is limited. This study addressed chlorophyll-breakdown-pathways (Chl-BP) on a seasonal basis from eight major ports (18–30 stations/port) representing freshwater, estuarine, and marine ecosystems. The distribution of chlorophyll and its breakdown fractions (pheophytin, pheophorbide) exhibited distinct spatial and seasonal variations. Fresh-water (except Haldia-port) and estuarine ports are characterized by high-biomass, high-pheophytin, and low-pheophorbide, whereas marine-ports by low-biomass (except Mangalore-port), low-pheophytin, and high-pheophorbide. Pheophytin and pheophorbide distribution were biomass independent and dependent, respectively. The pheophorbide: pheophytin ratio indicated a potential proxy for determining the dominant breakdown pathway, i.e., herbivory dominant (>1) or not dominant (<1). However, CHl-BP is taxa-specific and grazer's feeding habits. The ratios exhibited apparent differences between different ecosystems, i.e., the higher ratios in marine (up to 11.2) followed by estuarine (up to 0.9) and freshwater (up to 0.4; except Haldia) systems. The diatoms (preferred grazer diet) contribution to total phytoplankton was more in marine followed by estuarine and freshwater systems. The low and high ratios suggested the prevalence of chlorophyll-breakdown via senescence and grazing mode, respectively. We proposed that such scaling will have implications in the ballast water management – BWM (ballast tank conditions (eg. dark) during voyages, post-voyage discharge – including treated water using approved BWM systems, and the nature of ports, potential discharge point) and algal bloom research (e.g. understanding fate and in control measures). Highlights: Assessed chlorophyll breakdown pathway (ChlBP) from different ecosystems. Pheophorbide (Pb) & pheophytin (Pp) were biomass dependent & independent respectively. Pb/Pp ratio up to 0.4, 0.9 and 11.2 for freshwater, estuary, & marine ecosystems respectively. High & low Pb/Pp ratio suggests ChlBP via herbivory & senescence respectively.